MEKSIKO DAN MIKTA - leonard hutabarat (Universitas Pendidikan Nasional, 2017)
AbstractThis article argues that MIKTA (Mexico, Indonesia, South Korea, Turkey, and Australia) are middle, regional, and constructive powers that can serve as providers of global governance in the international system. It argues that in order for MIKTA countries to serve as middle, regional, and constructive powers, they need to consolidate the support of all relevant State and non-State actors in their countries, allowing MIKTA to become a relevant mechanism to promote and generate public goods in the international system, specially global governance. Mexico is the second largest economy in Latin America. Mexico is today an actor with global responsibility and obligatory reference. A country with that weight must play in new boards and MIKTA, constituting and innovative alliance with key non-traditional partners, is a strategic space to expand the scope of Mexican foreign policy. Keywords : MIKTA, middle powers, foreign policy, Mexico